Force-controlled dynamic wear testing of total ankle replacements. (15th January 2015) - Reinders, Jörn; von Stillfried, Falko; Altan, Emel; Sonntag, Robert; Heitzmann, Daniel W.W.; Kretzer, Jan Philippe
Graphical abstract: Abstract: Currently, our knowledge of wear performance in total ankle replacements is limited. The aim of this study is to develop a scenario for force-controlled testing and wear testing of total ankle replacements. A force-controlled wear test was developed: based on cadaver measurements, the passive stabilization (ligaments and soft tissue) of the ankle joint was characterized and a restraint model for ankle stabilization was developed. Kinematics and kinetics acting at the replaced ankle joint were defined based on literature data and gait analysis. Afterwards, force-controlled wear testing was carried out on a mobile, three-component, total ankle replacement design. Wear was assessed gravimetrically and wear particles were analyzed. Wear testing resulted in a mean wear rate of 18.2 ± 1.4 mm 3 /10 6 cycles. Wear particles showed a mean size of 0.23 μm with an aspect ratio of 1.61 ± 0.96 and a roundness of 0.62 ± 0.14. Wear testing of total ankle replacement shows that a relevant wear mass is generated with wear particles in a biologically relevant size range. The developed wear test provides a basis for future wear testing of total ankle replacements.